2021
DOI: 10.1210/clinem/dgab684
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Cytokines Throughout Pregnancy in Women With Polycystic Ovary Syndrome

Abstract: Context Polycystic ovary syndrome (PCOS) is a common endocrine disorder associated with low-grade inflammation and increased incidence of pregnancy complications, but its influence on the maternal immune system in pregnancy is unknown. Longitudinal serum cytokine profiling is a sensitive measure of the complex immunological dynamics of pregnancy. Objective Determine the immunological dynamics of serum cytokines throughout pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Elevated expression of programmed cell death protein 1 (PD-1) in both CD4 + /CD8 + T cells of FF showed a positive association with serum estradiol levels [123]. Cytokine analysis in pregnant PCOS women showed notable participation of tumour necrosis factor α (TNF-α) and IL-8 in all terms and IL-2, C-reactive protein (CRP), IL-1β, IL-12, and IL-6, in initial pregnancy stages, strongly points to the pregnancy complications observed in PCOS women [124]. Several studies conducted in different ethnic population have reported the involvement of pro-inflammatory cytokine in the immunopathogenic condition of PCOS.…”
Section: Hormonal Imbalance and Cytokines In Pcosmentioning
confidence: 86%
“…Elevated expression of programmed cell death protein 1 (PD-1) in both CD4 + /CD8 + T cells of FF showed a positive association with serum estradiol levels [123]. Cytokine analysis in pregnant PCOS women showed notable participation of tumour necrosis factor α (TNF-α) and IL-8 in all terms and IL-2, C-reactive protein (CRP), IL-1β, IL-12, and IL-6, in initial pregnancy stages, strongly points to the pregnancy complications observed in PCOS women [124]. Several studies conducted in different ethnic population have reported the involvement of pro-inflammatory cytokine in the immunopathogenic condition of PCOS.…”
Section: Hormonal Imbalance and Cytokines In Pcosmentioning
confidence: 86%
“…Furthermore, these elevated concentrations were found to exhibit a positive correlation with the insulin resistance states commonly associated with PCOS [ 79 ]. Moreover, a recent paper identified increased serum CXCL8 and CXCL10 levels at week 10 of pregnancy in PCOS women [ 80 ]. Nevertheless, no variations were noted in the CXCL10 levels between non-obese, non-IR PCOS women and controls [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a strong risk factor for pre-eclampsia, 25 and women with PCOS are more often obese than women without PCOS. 19 Obesity and pre-eclampsia are both associated with insulin resistance, inflammation and oxidative stress, 25,43,44 factors that may affect the association.…”
Section: Discussionmentioning
confidence: 99%